Harm reduction through housing first: an assessment of the Emergency Warming Centre in Inuvik, Canada. Issue 1 (December 2017) - Young, Michael; Manion, Kathleen
Abstract Background This research examines the effectiveness of an Emergency Warming Centre (EWC) in Inuvik, Canada, at reducing rates of morbidity and mortality for homeless persons with concurrent disorders (mental health problems and addictions). Inuvik is a small town of approximately 3500 residents, with over 65% being Aboriginal. The town is situated on the Beaufort Delta in the Western Canadian Arctic and is subject to oil and gas extraction-based boom and bust economic cycles. The centre provided food and accommodation for those under the influence of alcohol or drugs who had no other place to stay. Methods Qualitative interviews about users' experiences at the centre were conducted with guests, as they were called, centre staff and other key stakeholders in autumn 2014 and spring 2015. Samples of (9) respondents and (7) stakeholders provided significant information about the importance of the EWC. The content of the qualitative data with guests and stakeholders were analyzed for emergent themes. Results Several emergent themes and subthemes related to participants' experiences at the EWC and success of the centre. Overall, the results showed that guests benefitted from a safe place to stay and felt better about their overall health. Conclusions Compared with research on wet shelters in New Zealand, Great Britain and the US, this research reveals that harm reduction-based models for homeless persons with concurrent disorders require significant investments in infrastructure, which are not readily available. Yet, the lessons learned from these jurisdictions might be extrapolated to communities like Inuvik to develop alternative housing strategies.